Electrospun one-dimensional electrocatalysts for boosting electrocatalysis. Issue 36 (7th September 2022) - Ding, Changming; Qiao, Zhiyong
Abstract : Electrospun 1D nanomaterials are highly active towards the electrocatalytic energy conversion reaction. Abstract : The electrocatalytic reaction plays a crucial role in determining the energy conversion efficiency in advanced technologies. However, it is limited by the sluggish reaction kinetics and high energy barrier. These shortcomings necessitate the construction of 1D nanocatalysts with abundant catalytically active sites, high electrical conductivity, and easy tunable composition. Electrospinning has been demonstrated to be the most promising strategy for the fabrication of well-defined 1D nanostructures since it is highly efficient, ecofriendly, and economical. Herein, a comprehensive review regarding the design and development of advanced electrospun nanomaterials for electrocatalytic reactions has been summarized. First, the related fundamentals of electrospinning have been discussed. Second, the distinctive advantages of electrospun materials have also been summarized. Third, we have also summarized the structure design and catalytic properties of electrospun 1D nanocatalysts for boosting electrocatalytic energy conversion. Finally, a perspective on future directions and challenges for the fabrication of next-generation 1D electrospun nanocatalysts is also provided.